Corruption in poor and rich nations : a comparative review / Ademola Eyitope Ojo and Ayowale Collins Ojo - Ojo, Ademola Eyitope; Ojo, Ayowale Collins (Research Management Institute (RMI), 2012)
Corruption is no doubt endemic in every society. Its prevalence and longevity is a matter of concern and for its damaging public and social consequences undermines the development capacities of nations and distorts priorities. However, reports, incidents of corruption cases and discourse have concentrated on poor developing nations as presumed den of the corrupts. Hence, this paper comparatively reviewed data obtained from World Corruption Perception Index (Transparency International) for the year of2010, 2008, 2006 and 2004. The paper reveals that while poor nations are ranked higher in corruption indices, considerable numbers of rich developed nations are not exempted from corruption, particularly the G8 member nations. It is concluded that the earlier concept of corruption being peculiar amongst developing poor nations is evidentially overtaking by emerging consensus that corruption is a serious global epidemic. Thus it is recommended that national governments and international organizations must examine the roles of both the internal and external actors across nations to intensify policy measures and reforms to curb corruption between and within poor and rich nations.